GAME-BASED LEARNING SEBAGAI STRATEGI UNTUK MENINGKATKAN KEMAMPUAN ANALISIS TEKS CERPEN DALAM MATA PELAJARAN BAHASA INDONESIA - Rani Setiyani; Sri Wulan Maharani; Ichsan Fauzi Rachman (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This study aims to examine the effectiveness of the Game-Based Learning (GBL) strategy in improving short story text analysis skills in Indonesian language learning. The background of this study stems from the low interest and student engagement in literature learning, particularly short stories, which have often relied on conventional, less interactive methods. Using the literature review method, this study analyzes various scholarly sources such as journals, theses, and academic articles published between 2020 and 2024. The findings indicate that GBL can significantly enhance learning motivation, student engagement, and academic achievement in short story analysis. The use of educational game platforms such as Wordwall, Baamboozle, and Scorative is proven to be effective in helping students understand intrinsic and extrinsic elements of short stories in a fun and meaningful way. GBL also promotes collaborative and contextual learning, aligning with the needs of 21st-century learners. Therefore, GBL can be considered a relevant and applicable alternative strategy to improve literary text analysis skills in schools.